The Effectiveness of Group Counseling with Rational Emotive Behavior Therapy (REBT) in Reducing Student Anxiety in Facing Exams - Arnita, Fitri; Netrawati, Netrawati (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The background of this research is based on the anxiety problems that often occur in students when facing an exam. This can be seen in students when taking exams‚ students often experience anxiety symptoms such as cold sweats‚ tremors‚ sleeping difficulty when exam day is near. Efforts made in dealing with this challenge are group counseling using a rational emotive behavior therapy approach. This research aims to see the effectiveness of group counseling with a rational emotive behavior therapy approach in reducing anxiety in facing exam students. This study uses an experimental design with a pretest and post-test control group design. The subjects in this study were students of SMAN 13 Padang. This study uses an experimental design with a pretest and post-test control group design. The subjects in this study were students of SMAN 13 Padang, who revealed sixteen students with high and moderate anxiety categories. The instrument used in this study is the instrument to face the test with a Likert scale. The population in this study are students of SMAN 13 Padang, with seven samples in the control group and 7 in the experimental group. The technique used is the Purposive sampling technique. The data were analyzed using the Wilcoxon Signed Rank Test and the Kolmogorov Smirnov 2 Independent Sample test with the help of SPSS version 20.00. The results of this study indicate that group counseling with a rational emotive behavior therapy approach effectively reduces students' anxiety in facing exams.